INFLUENCE OF PUBLIC RELATIONS IN LOCAL GOVERNMENT ADMINISTRATION IN DELTA, EDO AND RIVERS STATES OF SOUTH-SOUTH NIGERIA - Mavis Okeoghene Onojeghwo; Ovie Victor Otubue; Eloho Patience Oziwele; Angela Nkiru Nwammuo (ADMIN: Jurnal Administrasi Negara, 2026)
Public relations is a strategic communication function that promotes mutual understanding and goodwill between organizations and their publics. Despite its importance, many local government councils in Nigeria either lack effective public relations structures or fail to utilize them adequately in public administration. This study examined the influence of public relations on local government administration in Delta, Edo, and Rivers States, Nigeria. Three local government areas were randomly selected from each state, resulting in a total of nine local government councils. Data were collected through interviews and questionnaires. Senior staff members of the selected councils were interviewed, while 1,283 questionnaires were distributed to both council employees and members of the public. A total of 1,222 valid responses were retrieved and analyzed using percentages and mean scores. The findings revealed that all the selected councils had public relations units, although most operated under the designation of Public Affairs Departments. However, respondents perceived these units as ineffective in addressing public concerns and managing crises. The study further found that effective public relations practice has the potential to positively influence public opinion and improve the image of local government administration. Nevertheless, public relations remains underutilized in many local government councils, limiting its contribution to grassroots governance and public engagement. The study concludes that public relations is a vital instrument for enhancing transparency, accountability, and citizen participation in local government administration. It recommends the establishment and strengthening of professional public relations units in all local government councils to improve government-public relations and promote good governance at the grassroots level.